2022
DOI: 10.3390/nu14020244
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Dietary Intake with Arterial Stiffness and Vascular Ageing in a Population with Intermediate Cardiovascular Risk—A MARK Study

Abstract: The aim of this study was to analyse the association of diet with arterial stiffness and vascular ageing in a Caucasian population with intermediate cardiovascular risk. We recruited 2475 individuals aged 35–75 years with intermediate cardiovascular risk. Brachial-ankle pulse wave velocity (baPWV) was measured using a VaSera VS-1500® device. Vascular ageing was defined in two steps. Step 1: The 20 individuals who presented kidney disease, peripheral arterial disease, or heart failure were classified as early v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The weight loss program in obese patients is based on diet changes and regular exercise [ 59 , 60 , 61 ]. In a review article prepared by Saladini et al, it has been shown that in a large number of studies regular exercise training, in MS patients, is confirmed to provide benefits not only in reducing body weight, decreasing BP, and improving metabolic profile but also in reducing sympathetic activity which leads to better endothelial function and arterial elasticity.…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…The weight loss program in obese patients is based on diet changes and regular exercise [ 59 , 60 , 61 ]. In a review article prepared by Saladini et al, it has been shown that in a large number of studies regular exercise training, in MS patients, is confirmed to provide benefits not only in reducing body weight, decreasing BP, and improving metabolic profile but also in reducing sympathetic activity which leads to better endothelial function and arterial elasticity.…”
Section: Impact Of Metabolic Syndrome Components On Arterial Stiffnessmentioning
confidence: 99%
“…The cut-off value of 1.06 was based on the median of PAD/AoD ratio increase. The median is a common and practical cut-off value classification method, which can be found in continuous variables such as clinical indicators ( 26 ), laboratory indicators ( 27 , 28 ), and imaging indicators ( 29 ), and pathological indicators ( 30 , 31 ). Figure 1F depicts the PAD/AoD ratio before and after ICIs with standard deviation and data points.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial stiffness is a significant prognostic factor influencing cardiovascular risk, which dietary habits can modify. [12][13][14][15] Perivascular adipose tissue is a fat depot not widely studied yet and has direct and profound effects on arterial stiffening. [16][17][18] Furthermore, it has been shown that aortic (central) pulse pressure is a better cardiovascular events predictor than brachial pulse pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It is also one of the earliest indicators of increased CVD risk and can be considered a good predictor of the development of subclinical cardiovascular dysfunction. Arterial stiffness is a significant prognostic factor influencing cardiovascular risk, which dietary habits can modify 12–15 . Perivascular adipose tissue is a fat depot not widely studied yet and has direct and profound effects on arterial stiffening 16–18 …”
Section: Introductionmentioning
confidence: 99%